Autologous Hair Follicle Transplantation Combined with NB-UVB Phototherapy for Stable Pubic Vitiligo: A Randomized Controlled Trial - Wei, Xinyu; Osman, Muhamed T. (Trends in Immunotherapy, 2026)
The challenge in the management of pubic vitiligo lies in the sensitive nature of the area and the relatively lower efficacy of the existing management approaches. This study aimed to evaluate the efficacy and safety of autologous hair follicle transplantation combined with narrow-band ultraviolet B (NB-UVB) phototherapy for stable pubic vitiligo. Sixty-eight patients were randomly assigned (1:1) to either a combination treatment (hair follicle transplantation followed by NB-UVB phototherapy) or to the control group with only NB-UVB phototherapy for 24 weeks. The key outcome measure was the repigmentation area, as estimated using the Vitiligo Area Scoring Index. The histopathological examination was also carried out on a sample of 40 patients. The combination therapy group demonstrated significantly higher repigmentation rates (68.4% versus 42.3%, p < 0.001). The effective response rate (≥50% repigmentation) was 80.6% versus 43.3% (p = 0.003). The onset of repigmentation occurred earlier in the combination group (4.2 versus 7.6 weeks, p < 0.001), where there was perifollicular repigmentation in 83.9% of patients. Histopathological examination revealed that there was a greater increase in the density of melanocytes (10.4 versus 4.8 cells/mm, p < 0.001) and a greater reduction in the density of CD8+ T cells in the combination group. Patient satisfaction was significantly higher among the combination group (87.1% versus 53.3%, p = 0.004). Tolerance of these two treatments is excellent, and there were no serious adverse events. This combination of hair follicle transplantation and NB-UVB appears to have a synergistic effect, as it offers an intact melanocyte reservoir and an immune microenvironment, and it may be a promising treatment approach for pubic vitiligo.